(untitled) (Research, Society and Development, 2022)
Introduction: Microwave-cured polymethylmethacrylate (MCPM) are commonly used in dentistry due low cost, transparency and easy handling. However, do not have a long useful life, due to their chemical fragility and low hardness and wear resistance. Aim: Assessing the effect of a diamond-like carbon (DLC) film coating on the mechanical and surface properties of MCPM. Methodology: The MCPM samples were divided into control (Gc) and treatment (Gt) groups, and were subjected to flexural strength (n=18), wear resistance (n=18) tests, and to topography and surface roughness (Ra) analysis by three-dimensional optical profilometry (n=18). The films were deposited by plasma-enhanced chemical vapor deposition. Differences between groups were assessed by the Mann-Whitney and t tests using a 5% significance level (p<0.05). Results: The Gt had higher surface roughness (0.108 ± 0.01µm) than the Gc (0.038 ± 0.01µm), with p<0.0001. No significant difference (p=0.606) in flexural strength was found between Gt (103.3 MPa) and Gc (105.3 MPa). No significant difference was found between the groups in terms of straightness (Gt: 0.006 ± 0.0059 mm and Gc 0.005 ± 0.0052mm, p=0.774) or indentation depth (Gt: 29.974 ± 8.69µm and Gc: 28.169 ± 5.71µm, p=0.610) after the wear test. Conclusion: Coating the MCPM surface with a DLC film affected the surface roughness, with no effects on flexural strength and wear resistance. New studies are suggested to better understand these effects, perhaps with variations in the deposition parameters such as coating thickness or on the sp3/sp2 ratio.